Drosophila microRNA-34 Impairs Axon Pruning of Mushroom Body ? Neurons by Downregulating the Expression of Ecdysone Receptor. - Lai, Y.W.; Chu, S.Y.; Wei, J.Y.; Cheng, C.Y.; Li, J.C.; Chen, P.L.; Chen, C.H.; Yu, H.H. (Scientific reports, 2016)
MicroRNA-34 (miR-34) is crucial for preventing chronic large-scale neurite degeneration in the aged brain of Drosophila melanogaster. Here we investigated the role of miR-34 in two other types of large-scale axon degeneration in Drosophila: axotomy-induced axon degeneration in olfactory sensory neurons (OSNs) and developmentally related axon pruning in mushroom body (MB) neurons. Ectopically overexpressed miR-34 did not inhibit axon degeneration in OSNs following axotomy, whereas ectopically overexpressed miR-34 in differentiated MB neurons impaired ? axon pruning. Intriguingly, the miR-34-induced ? axon pruning defect resulted from downregulating the expression of ecdysone receptor B1 (EcR-B1) in differentiated MB ? neurons. Notably, the separate overexpression of EcR-B1 or a transforming growth factor- ? receptor Baboon, whose activation can upregulate the EcR-B1 expression, in MB neurons rescued the miR-34-induced ? axon pruning phenotype. Future investigations of miR-34 targets that regulate the expression of EcR-B1 in MB ? neurons are warranted to elucidate pathways that regulate axon pruning, and to provide insight into mechanisms that control large-scale axon degeneration in the nervous system.